The Italian National Rare Diseases Registry - Taruscio, Domenica (Edizioni SIMTI - SIMTI Servizi Srl, 2014)
INTRODUCTION: Rare disease registries are a priority at European level and specific actions are being implemented by the European Commission to support their development. In Italy, a National Registry of rare diseases has been established in 2001 as a network of regional registries. The latter have gradually been established and the full coverage of the Italian territory was attained during 2011. METHODS: Here we describe the basic features of the National Registry of rare diseases; the activities carried out to promote consistent operations in the regional registries; and the overall quality and composition of the records collected. RESULTS: After a validation process, including removal of duplicate records, 110,841 records of patients with rare diseases, single and with group denominations, are stored in the National Registry of rare diseases. They correspond to the overall diagnoses communicated to national registry by regional registries up to 30 June 2012. The quality of the data collected by the the National Registry of rare diseases has been assessed with respect to completeness and consistency of procedures. Variables characterising case and diagnosis showed a very limited number of missing values. Records reported at least one case of 485 rare conditions. DISCUSSION: To date, the National Registry of rare diseases is a surveillance system with the main objective of producing epidemiologic evidence on rare diseases in Italy, and of supporting policy making and health services planning. Data quality still represents a limitation for any sound epidemiological estimate of rare diseases in Italy. However, improvements of the quality of collected data and the completeness of case notifications should be strengthened.